ReGeneraTing Agents (RGTA®) are a new option to improve amputation outcomes in the recovery of severe hand injuries - Syed Waseem Ahmad, Sharifah Roohi; Barritault, Denis (Wiley Open Access, 2018)
CACIPLIQ20® was used to accelerate the healing process and stimulate the viability of flaps and skin grafts, thereby improving amputation outcomes. An excellent range of motion was achieved with hardly any contracture or scarring. Pain relief and reduced sensitivity was noted, while healing of bone and tendon also improved, resulting in functional recovery.